Meta-Analysis of the Efficacy of Laparoscopic Pyeloplasty for Ureteropelvic Junction Obstruction via Retroperitoneal and Transperitoneal Approaches - Ji, Fengming; Chen, Li; Wu, Chengchuang; Li, Jinrong; Hang, Yu; Yan, Bing (Frontiers in Pediatrics, 2021)
Objective: This study aimed to evaluate the clinical efficacy of laparoscopic pyeloplasty (LP) for ureteropelvic junction obstruction (UPJO) via retroperitoneal and transperitoneal approaches. Method: A systematic literature search on keywords was undertaken using PubMed, Cochrane Library, Embase, China Nation Knowledge (CNKI), and Wanfang. The eligible literature was screened according to inclusion and exclusion criteria. Meta-analysis was performed by using RevMan 5.0 software. Results: According to the inclusion and exclusion criteria, 12 studies were identified with a total of 777 patients. Four hundred eight patients were treated with retroperitoneal laparoscopic pyeloplasty (RLP), and 368 patients were treated with transperitoneal laparoscopic pyeloplasty (TLP). The meta-analysis results showed that the two approaches were similar in terms of presence of postoperative hospital stay, postoperative complication, the rate of conversion, and recurrence (p > 0.05). The operative time in the TLP group was significantly shorter than the RLP group (MD = 16.6; 95% CI, 3.40–29.80; p = 0.01). The duration of drainage was significantly shorter (MD = −1.06; 95% CI, −1.92 to −0.19; p = 0.02), and the score of postoperative visual analog score (VAS) was significantly lower in the RLP group than in the TLP group (MD = −0.52; 95% CI, −0.96 to −0.08; p = 0.02). Conclusion: Both approaches have good success rates and low postoperative complication rates. RLP provides a shorter duration of drainage and lower VAS score, but it takes more operative time than TLP.